Analisis Strategi Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru dan Kualitas Pembelaran IPAS di SMAN 24 Pangkep - Sumarni, Sumarni; Devilla, Rego; W, Muhammad Fahreza (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study aims to analyze the role of the principal's strategy in improving teacher professionalism and the quality of social studies learning at SMAN 24 Pangkep. This research is a qualitative research with a descriptive approach. The subjects in this study are the principal, supervisor, deputy principal and 3 science and technology maple teachers. The data collection techniques in this study use interviews, observations, and documentation while the data analysis techniques used include data reduction, data presentation, and conclusion drawn/verification.  The results of the study show that the strategy of the principal of SMAN 24 Pangkep in improving teacher professionalism has shown positive results, especially in curriculum development and teacher training. However, there is a need to improve teacher performance evaluation as well as monitoring and evaluating programs so that the results achieved are more optimal and sustainable. In terms of the quality of IPAS learning, learning planning and media facilitation as well as learning resources at SMAN 24 Pangkep have been going well. However, learning supervision and evaluation and follow-up on programs need to be improved to ensure the effectiveness and continuity of learning development. The improvement of teacher professionalism and the quality of science and technology learning at SMAN 24 Pangkep faces several obstacles, such as limited teacher competence in mastering innovative methods, lack of support for learning facilities, and lack of teacher training. In addition, obstacles in external cooperation also reduce the effectiveness of teaching and teacher competency development. To overcome these obstacles, solutions that can be implemented include the development of relevant teacher training programs, the provision of adequate learning facilities, and the optimization of school resources. Increased collaboration with external parties also needs to be done to support innovation and sustainability of educational development at SMAN 24 Pangkep.